Facebook marketing for dummies - Dunay, Paul; Krueger, Richard (Hoboken, N.J. Wiley, 2011)
Recruit fans and turn them into customers! This book makes it easy to create a page, add applications to it, host an event, and much more. It's an easy-to-follow blueprint for marketing and promoting your organization on Facebook!
Introduction -- Adding Facebook to your marketing strategy -- Building your Facebook presence -- Engaging in Facebook advertising -- Riding the Facebook viral wave -- The part of tens -- Appendix: The Facebook primer.
Previous ed.: 2010.
Keywords: Facebook (Electronic resource).; Internet marketing; Internet advertising